2017
DOI: 10.1186/s12871-017-0443-y
|View full text |Cite
|
Sign up to set email alerts
|

Chronic administration of parecoxib exerts anxiolytic-like and memory enhancing effects and modulates synaptophysin expression in mice

Abstract: BackgroundPrevious studies have shown that cyclooxygenase-2, a key enzyme that converts arachidonic acid to prostaglandins, is involved in anxiety and cognitive processes, but few studies have investigated the effects of chronic administration of cyclooxygenase-2 inhibitors on anxiety, learning and memory under normal physiological conditions. The aim of the study was to investigate the effects of chronic administration of parecoxib, a cyclooxygenase-2 inhibitor, on anxiety behavior and memory performance unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Indeed, peripheral COX-2 expression is increased in some patients with major depression (Galecki et al, 2012, 2014). Importantly, pharmacological inhibition of COX-2 has shown promise in preclinical animal models of anxiety-like and depressive-like behaviors (Hermanson et al, 2013; Gamble-George et al, 2016; Wang et al, 2017; Myint et al, 2007; Guo et al, 2009), and in clinical trials, when used as an augmentation strategy with SSRI treatment in patients with major depression (Akhondzadeh et al, 2009; Faridhosseini et al, 2014). These findings suggest COX-2 inhibition may represent a novel approach for the treatment of affective disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, peripheral COX-2 expression is increased in some patients with major depression (Galecki et al, 2012, 2014). Importantly, pharmacological inhibition of COX-2 has shown promise in preclinical animal models of anxiety-like and depressive-like behaviors (Hermanson et al, 2013; Gamble-George et al, 2016; Wang et al, 2017; Myint et al, 2007; Guo et al, 2009), and in clinical trials, when used as an augmentation strategy with SSRI treatment in patients with major depression (Akhondzadeh et al, 2009; Faridhosseini et al, 2014). These findings suggest COX-2 inhibition may represent a novel approach for the treatment of affective disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The level of synaptophysin and PSD95 decreased in scopolamine induced Alzheimer disease mice in comparison to control group while it was up regulated in the scopolamine plus folicitin and only folicitin injected mice. Studies have shown that the level of synaptophysin decreased with amyloid beta disposition, progressive aphasia and dementia [ 104 , 105 , 106 , 107 ]. PSD95 is an important post synaptic protein which is required for the structure and function of brain cells [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…SYP, a major calcium-binding protein of the synaptic vesicle membrane, accurately reflects the distribution, number, and density of synapses. Y-maze experiments have shown that increased hippocampal SYP levels contribute to new object recognition and learning and memory improvement in mice [27]. GAP-43, a neuron-specific protein, is located in the axon and maintains synaptic morphology [28].…”
Section: Discussionmentioning
confidence: 99%